(3TQM GdbBGfi Ydi GdeZfis - (3CHh eMeO efUhQ Hf CMeO Hf GdeDjO GdNhGQRei GdbGBfis; (3YeQ Hf eMeO Hf YeQ GdNHGRj GdNLfOj, CHh eMeO, LdGd GdOjf,J (B691 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd deG cGf GdeDefhf dGjced EjeGf GdYHO MJi jMH dCNjg eG jMH dfaSg s
(3BNQgG (B:s
(3Chdi ef LYdgG eLGRkG Yf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B315s
Keywords: (3CUhd Gdabgs